2012
DOI: 10.1111/j.1399-3089.2011.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Gal expression on pig cells on the human T‐cell xenoresponse

Abstract: Background Lack of Gal expression on pig cells is associated with a reduced primate humoral immune response as well as a reduction in cytokine production by human cells in vitro. We investigated whether lack of Gal expression is associated with reduced human T-cell response in vitro. Methods Peripheral blood mononuclear cells (PBMCs) were obtained from healthy humans and naïve baboons. Human CD4+ and CD8+ T cells were isolated. Porcine aortic endothelial cells (pAECs) were isolated from wild-type (WT) and α1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…In particular, porcine endothelial cells constitutively express CD80/CD86 (Koshika et al 2011) and SLA class I, and possibly class II molecules as well (Choo et al 1997). Porcine endothelial cells also trigger a direct, MHC-restricted CD8 þ T-and CD4 þ T-cell activation (Yamada et al 1995;Dorling and Lechler 1998;Kim et al 2010;Koshika et al 2011;Wilhite et al 2012). High levels of cytotoxicity have also been detected, mediated mainly by CD4 þ T cells, but also by CD8 þ T cells.…”
Section: Cell-mediated Xenograft Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, porcine endothelial cells constitutively express CD80/CD86 (Koshika et al 2011) and SLA class I, and possibly class II molecules as well (Choo et al 1997). Porcine endothelial cells also trigger a direct, MHC-restricted CD8 þ T-and CD4 þ T-cell activation (Yamada et al 1995;Dorling and Lechler 1998;Kim et al 2010;Koshika et al 2011;Wilhite et al 2012). High levels of cytotoxicity have also been detected, mediated mainly by CD4 þ T cells, but also by CD8 þ T cells.…”
Section: Cell-mediated Xenograft Rejectionmentioning
confidence: 99%
“…Analyzing in vitro lymphocyte proliferation induced by wild-type or GalT-KO endothelial cell shows that aGal epitope expression on the endothelium is associated with a greater proliferation of CD4 þ and CD8 þ T cells (Lin et al 2008;Wilhite et al 2012), suggesting an as-yetunidentified role of aGal epitopes in sustaining T cell response. The absence of aGal is also associated with a significantly reduced secretion of INF-g, TNF-a, IL-17A by CD4 þ T cells, and of INF-g, granzyme-B, and the chemokine IP-10 by CD8 þ T cells (Wilhite et al 2012), partially confirming earlier findings reported by Saethre et al (2008), who showed that exposure to Gal þ/þ endothelial cells was associated with a significant release of human INF-g, human and porcine proinflammatory IL-6 and IL-8, and several human b chemokines, whereas this picture was not seen after exposure to Gal 2/2 cells (Saethre et al 2008). Unlike the report from Wilhite et al (2012), however, the T-cell-recruiting a-chemokine IP-10 in the Saethre study was induced in cells lacking the aGal epitopes.…”
Section: Cell-mediated Xenograft Rejectionmentioning
confidence: 99%
“…A comprehensive overview of the experimental transplantations in the years until 2013 is given by Cooper et al [35]. To demonstrate the development in the field, the longest survival times listed by Cooper et al [35] and survival times published later [6,[36][37][38][39][40][41][42][43] are summarized in Tables 1 and 2. The ability to modify pigs genetically to protect the donor organs from the primate's immune response has resulted in survival of heterotopic pig hearts in baboons for longer than 2.5 years [39-41,44,45] ( Table 1).…”
Section: Increased Survival Timesmentioning
confidence: 99%
“…Animals expressing different combinations of the complement-regulatory proteins have been created (for overview, see Table 2 in [5]). In addition, immune T cell responses were reduced by simultaneous expression of CTLA4-IgG and mutant MHC class II transactivator [6][7][8][9]. a-gal epitopes and 2 N-glycoylneuraminic acid-terminated (Neu5Gc) gangliosides are targets for pre-existing antibodies in human sera [10].…”
Section: Immunological Rejectionmentioning
confidence: 99%
“…Depletion of alpha-gal epitopes by decellularization or by alpha-galactosidase treatment might reduce the humoral-and cellular-mediated immune responses. 8,52,53 Therefore, appropriate test systems for these epitopes should be applied in addition to the tests described in our study for a proper selection of suitable ECM components.…”
mentioning
confidence: 99%